Factors Related to the Productivity Level of Tofu Processing Workers at the Doa Ibu Tofu Factory in East Jakarta - Muhammad Syafhaa, Haykhal; Dwi Rahmah Rusdy, Mirta; Alia Keumala Muda, Cut; Shorayasari, Susi (LPPM Universitas Mohammad Husni Thamrin, 2025)
Work productivity is a crucial factor in determining the success of an organization or company. In the informal sector, productivity is often not formally recorded, but can be estimated through indirect indicators such as production output, work completion duration, and frequency of labor involvement. Labor productivity is a key determinant in ensuring the effectiveness and efficiency of the production process. Several factors are known to influence productivity levels, including work climate, nutritional status, and individual characteristics such as age, gender, education level, and length of service. This study aims to analyze factors related to the productivity levels of tofu processing workers at the Doa Ibu Tofu Factory in East Jakarta. This study used a quantitative approach with a cross-sectional design. The entire population of 34 processing workers was sampled using a total sampling technique. Data collection was carried out through direct measurements using WBGT (work climate), Body Mass Index (nutritional status), and questionnaires (age, gender, education, length of service, and productivity). Some respondents were recorded as having low productivity levels (50%). The results of the chi-square analysis showed that there was no significant relationship between the variables of work climate (p = 1,000), nutritional status (p = 0.214), age (p = 0.335), gender (p = 1,000), education (p = 0.398), and length of service (p = 1,000) on productivity (p > 0.05). However, monitoring working conditions and nutritional status is still recommended as an effort to increase workforce productivity.